A Case of Foreign-Body Granuloma of the Glabella due to Polyacrylamide Filler and an Intractable Ulcer after Skin Biopsy: An Immunohistochemical Evaluation of Inflammatory Changes - Kio Park; Fuyuko Nishiwaki; Kenji Kabashima; Yoshiki Miyachi (Case Reports in Dermatology, 2013)
Introduction: Polyacrylamide hydrogel has been considered a safe and biocompatible soft tissue filler, and it has been widely used in cosmetic procedures. However, recent studies have revealed some complications with polyacrylamide filler injections. Case Report: We present the case of foreign-body granulomas of the glabella, which subsequently formed an infectious ulcer 3 years after a polyacrylamide injection. An immunohistochemical evaluation of the foreign-body granulomas was performed in order to study the relationship between foreign-body granulomas and immune response. Conclusion: We believe that our analysis of foreign-body granulomas 1 and 3 years after a filler injection may contribute to revealing the mechanism of chronic and intractable infections after filler injections.